2014
DOI: 10.1002/2013ja019115
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of properties of small transients in the solar wind 2007–2009: STEREO and Wind observations

W. Yu,
C. J. Farrugia,
N. Lugaz
et al.

Abstract: We present a comprehensive statistical analysis of small solar wind transients (STs) in [2007][2008][2009]. Extending work on STs by Kilpua et al. (2009) to a 3 year period, we arrive at the following identification criteria: (i) a duration < 12 h, (ii) a low proton temperature and/or a low proton beta, and (iii) enhanced field strength relative to the 3 year average. In addition, it must have at least one of the following: (a) decreased magnetic field variability, (b) large, coherent rotation of the field vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 55 publications
11
55
0
Order By: Relevance
“…Higginson et al (2017c) have demonstrated that the 3D structure of reconnection-generated magnetic islands in the heliospheric current sheet are consistent with the observations of small-scale flux rope transients in the slow solar wind (Feng et al 2008;Cartwright & Moldwin 2008Kilpua et al 2009;Yu et al 2014). And Janvier et al (2014) have argued that the power-law distribution of the sizes of these small flux rope transients appears compatible with the power-law distributions of magnetic island plasmoids obtained in various reconnection studies (e.g.…”
supporting
confidence: 74%
“…Higginson et al (2017c) have demonstrated that the 3D structure of reconnection-generated magnetic islands in the heliospheric current sheet are consistent with the observations of small-scale flux rope transients in the slow solar wind (Feng et al 2008;Cartwright & Moldwin 2008Kilpua et al 2009;Yu et al 2014). And Janvier et al (2014) have argued that the power-law distribution of the sizes of these small flux rope transients appears compatible with the power-law distributions of magnetic island plasmoids obtained in various reconnection studies (e.g.…”
supporting
confidence: 74%
“…To derive the electron contribution to the plasma pressure, we use the result of Newbury et al [], who gave an estimate for T e based on data from the ISEE spacecraft. They obtained T e =1.42 × 10 5 K. Yu et al [, Figure 21] studied Wind data for the 3 years 2007–2009 and obtained for T e the average value of 1.51 × 10 5 K, which is close to Newbury et al 's [] result. Therefore, when examining STEREO data, we use T e =1.42 × 10 5 K, and let N e = N p when we calculate the β plasma .…”
Section: Methodssupporting
confidence: 69%
“…For it to be classified as Alfvénic, we require all three correlations to be greater than 0.5 or two greater than 0.6 and the other greater than 0.3, which is similar to the criterion in Cartwright and Moldwin []. Examples were given in Yu et al [, Figures 5 and 6].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Feng et al [] proposed that SIMFRs originate from the Sun and are interplanetary manifestations of small coronal mass ejections (CMEs). In addition, some authors discussed the origin of SIMFRs by investigating the possible relationship between SIMFRs and MCs and found that SIMFRs and MCs have many common and similar (or relative) characteristics [e.g., Feng et al , , , ; Cartwright and Moldwin, ; Feng and Wu, ; Yu et al , ; Janvier et al , , ; Feng and Wang, ]. These authors tend to agree with the view that SIMFRs originate from solar corona.…”
Section: Introductionmentioning
confidence: 92%